An 18th century Ottoman village in Central Anatolia: Sinason - Karasar, Hasan Ali (Cappadocia Journal of Area Studies, 2024)
This study examines the 18th-century Ottoman village of Sinason (modern-day Mustafapaşa, Ürgüp) through ten archival documents dated between 1696 and 1782, revealing its unique administrative, socio-economic, and legal dynamics. The village frequently shifted jurisdiction among Niğde, Kayseri, and Gülşehir, while its mixed population of Muslims and non-Muslims resulted in significant tax revenues. Documents highlight tax collection practices like avarız and nüzul, as well as integration into the tımar and vakıf systems supporting military and religious institutions, though these were sometimes exploited by local officials. Villagers faced issues like unjust taxation but effectively used Ottoman legal mechanisms to seek justice, reflecting trust in the central authority. Sinason’s economic contributions, including agricultural production and funding for imperial projects, demonstrate its importance within the Ottoman fiscal system. This analysis provides insights into rural life, governance, and justice during a period of significant geopolitical and economic challenges.